The Optimum Conditions for Naphthalene Biodegradation by Filamentous Fungi - B.Mohammed, Duha; Husein Khudeir, Saad; H.Al-Jubouri, Muna (Iraqi Journal of Science, 2023)
Recent studies have proved the important role of fungi in the biodegradation of oil pollutants. The present study aims to find the optimal conditions for the fungi to get the best rate of the biodegradation of the polycyclic aromatic hydrocarbon (PAHs) (Naphthalene) compounds. Soil samples were taken from 18 different sites polluted with oil wastes and cultured then obtained 312 isolated fungi from 64 replicates Primarily screening were done on fungal isolates on solid media containing naphthalene the results revealed that 25 fungal isolates gave good growth, 47 fungal isolates gave Moderate growth, 66 gave weak growth and 147 fungal isolates gave no growth on Naphthalene solid media.Then secondary screening were done on 25 fungal isolates the results showed that most active isolates were T1,MST2 and RS which were then identified as Aspergillus niger, Trichoderma viridi, Fusarium verticelloides, The results showed that the best time for Naphthalene biodegradation was 8 days for all fungal isolates (Aspergillus niger, Trichoderma viridi, Fusarium verticelloides) the best Naphthalene concentrations decline from 100 ppm to 12.22ppm was for Fusarium verticelloides , the best pH value for naphthalene degradation was 7 for all fungal isolate. The best Naphthalene concentrations decline from 100 ppm to 12.4 ppm was for Fusarium verticelloides, the best temperature for Naphthalene biodegradation was 30 0C for all fungal isolates, the concentrations of Naphthalene decline from 100 ppm to 12.6 ppm for Fusarium verticelloides, The results showed that the best concentration for Naphthalene biodegradation was 100ppm for all fungal isolates, the concentrations of Naphthalene decline from 100 ppm to 12.6 ppm for Fusarium verticelloides.